Impact of gaseous ozone coupled to passive refrigeration system to maximize shelf-life and quality of four different fresh fish products. (July 2018) - Aponte, Maria; Anastasio, Aniello; Marrone, Raffaele; Mercogliano, Raffaelina; Peruzy, Maria Francesca; Murru, Nicoletta
Abstract: The combined effect of ozone gaseous treatment and passive refrigeration system on microbiological, biochemical, and sensory changes of fresh cod ( Merluccius merluccius ), red shrimp ( Aristeus antennatus ), scald fish ( Arnoglossus laterna ) and musky octopus ( Eledone moschata ) was evaluated by monitoring quality during 12 days of storage. Except for hake, ozonation exerted a significant bactericidal effect on psychrotrophs, H2 S-producing bacteria, Aeromonas and Brochothrix spp. TVB-N and TMA-N experienced the same trend in the four fish types with higher increases in scald fish. The remarkable contents recorded in musky octopus for both parameters appeared to be due to autolytic activity. Except for red shrimp, the level of fat hydrolysis rarely appeared to be different within the ozonated and control samples. According to sensory assessment, ozonation may have a varying impact depending on the fish product: the treatment extended the scald fish shelf-life up to one week, while in red shrimp no difference occurred for the first week. Based on the outcomes, the combined approach developed here has proven to be an effective technology for fish shelf-life extension, with the best influence on microbial control in scald fish and musky octopus. At any rate, conditions for treatment need to be fine-tuned to the specific fish product. Graphical abstract: Highlights: Ozone and passive refrigeration were used to extend shelf life in four fish species. Analyzed fish products were cod, red shrimp, scald fish and musky octopus. Microbial, chemical, sensory aspects were evaluated. Ozonated and control samples were monitored up to 12 days. The combined approach proved to be effective for fish shelf life extension.